Drug-Induced Insomnia: Descriptive analysis of FDA Adverse Event Reporting System (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: Insomnia is one the most common problems encountered by the family physician and can occur due toseveral causes such as using some drugs. The present study aimed to describe the reports that were submitted toFDA Adverse Event Reporting System (FAERS) about drug-induced insomnia. Materials and Methods: TheFAERS was used to conduct this retrospective study that comprised a descriptive analysis of all reported adverseevents of drug-induced insomnia in the past 5 years. Results: During the study period from the beginning of2017 to the end of 2021, there were 86918 reports about drug-induced insomnia submitted to FAERS. The mostfrequently reported drugs were levothyroxine sodium (3.85%), duloxetine hydrochloride (3.24%), adalimumab(3.08%), pregabalin (2.71%), etanercept (2.17%), and niraparib (2.04%). Conclusion: It is important to increasethe awareness of healthcare workers about the medications that could cause insomnia. Moreover, health-careproviders should educate the patients about the drugs that could induce insomnia, how they can manage insomnia,and how they can report these adverse effects.